a)
2x - 3y = 7 | * -3
3x - 5y = 11 | * 2
-6x + 9y = -21
6x -10y = 22
------------------
-y=1
y=(-1)
2x- 3* (-1)= 7
2x=7-3
2x=4
x=2
b)
5p - 2r = 21 |*5
3p + 5r = -6 |*2
25p - 10r=105
6p+10r= -12
-----------------------
31p= 93
p= 3
5*3 - 2r =21
-2r=6
r=-3
c)
2x-3y=10 |*5
5x+5y=0 |* -2
10x-15y=50
-10x-10y=0
------------------
-25y=50
y= -2
2x- 3 * (-2) = 10
2x=4
x=2
d)
5v₁ + 4v₂ = 4 |* -5
7v₁+ 5v₂ = 6 |* 4
-25v₁ - 20v₂=-20
21v₁ + 20v₂ = 24
-----------------------
-4v₁=4
v₁=-1
5* (-1) +4v₂=4
4v₂= 9
v₂= 2¼